Comparison of Student Learning Outcomes Using Class Action Research To Improve Mathematics Problem Solving Ability - Hutajulu, Masta; Sofiah, Andita Aulia; Rustella, Friska; Syahpitri, Dita; Putri, Adisha Savira Rudiana; Harianti, Ayu (Universitas Wiralodra, 2023)
This study aims to determine the comparison of student learning outcomes using a scientific approach and learning model Problem Based Learning. This type of research uses the Classroom Action Research (CAR) method or can be referred to as (Classroom action research) and mix methods (Quantitative and Qualitative). The subject of this study was located at SMP Negeri 3 Cimahi in class VIII-I with a total of 34 students. Data collection techniques with pre-test and post-test. The results showed that there were differences in mathematical problem solving abilities between students who used a scientific approach and students who used the Problem Based Learning learning model. The results showed that the application of the Problem Based Learning model could improve students' mathematical problem solving abilities from cycle I to cycle 2 by 10%. The results of the research show that the Problem Based Learning (PBL) model can improve problem solving abilities in the material on the System of Two Variable Linear Equations (SPLDV). This research can be concluded that the ability to solve problems in SPLDV material can be increased by applying the problem based learning model.